2014
DOI: 10.1016/j.jpba.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of flavonoid aglycones as a result of the ex vivo deconjugation of glucuronides by the tissue β-glucuronidase

Abstract: Flavonoid glucuronides are the main circulating metabolites of flavonoids in humans and animals. There has been a growing interest in the biological function of glucuronides. In order to differentiate biological activity and to assess efficacy it is essential to accurately determine the levels of flavonoid aglycone and metabolic conjugate in vivo. Many organs and body fluids of humans and animals exhibit β-glucuronidase against flavonoid glucuronides. Studies have shown that β-glucuronidase within the tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Flavonol metabolism in body tissues is not well understood. An in vitro study suggested that β-glucuronidase enzyme found in body tissues hydrolyzes the conjugated metabolites producing aglycones [49]. Flavonol metabolites are excreted by urinary and biliary elimination.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Flavonol metabolism in body tissues is not well understood. An in vitro study suggested that β-glucuronidase enzyme found in body tissues hydrolyzes the conjugated metabolites producing aglycones [49]. Flavonol metabolites are excreted by urinary and biliary elimination.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Also, polyphenols may undergo ex vivo hydrolysis or secondary transformation during the hydrolysis process, further contributing to analytical variability. [16,17] Thus, when the goal is to determine overall exposure to a polyphenol, it is preferred to conduct a direct analysis of all possible plasma metabolites, that is, without hydrolysis. Such analyses, however, are often not practical and difficult to perform.…”
Section: Introductionmentioning
confidence: 99%
“…While simplifying the analyte profile, this practice also introduces novel sources of variability: Whether hydrolysis of plasma conjugates is complete is difficult to assess in the absence of direct analysis of the remaining parent conjugates. Also, polyphenols may undergo ex vivo hydrolysis or secondary transformation during the hydrolysis process, further contributing to analytical variability …”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that natural compounds from folk medicines or medicinal plants are still primary sources for discovering lead compounds or drug candidates [21]. A wide range of natural compounds with diverse scaffolds (e.g., quercetin, eugenol, and emodinol) have been reported with EcGUS inhibition activity over the past few decades [1,22], which inspired us to find more effective EcGUS inhibitors from folk medicines. Our preliminary screening found that the crude extract of Mulberry bark (also named Sang Bai Pi in Chinese) displayed relatively potent EcGUS inhibition with an IC 50 value of 0.68 µg/ml (Fig.…”
mentioning
confidence: 99%